Silane coupling and mordanting as attachment techniques for pyridylazo and thiazolylazo ligands in the synthesis of adsorbents for uranium in seawater - Grace M Pooley; Mohammad A Adel-Hadadi; Weixing Li; Travis C Dietz; Aaron Barkatt (Adsorption Science & Technology)
Activated carbon adsorbents modified with azo compounds (4-(2-pyridylazo)resorcinol, 1-(2-pyridylazo)-2-naphthol, 4-(2-thiazolylazo)resorcinol), or with allyl and vinylbenzyl derivatives of 4-(2-thiazolylazo)resorcinol, were observed to be highly effective in removing uranium from seawater and providing high loadings. Adsorbents consisting of azo compounds attached to fiber fabrics were prepared using silane coupling to attach azo reagents to silica fibers or mordanting agents such as tannic acid or aluminum acetate to attach them to cellulose fibers. Loadings of 15–45 mg U g −1 adsorbent were obtained. Scanning electron microscopy/energy dispersive X-ray spectroscopy measurements confirmed the presence of high concentrations of uranium on the surface of the silica-based and cellulose-based fibers.